Extraction of carotenoids from cantaloupe waste and determination of its mineral composition. (September 2018) - Benmeziane, Akila; Boulekbache-Makhlouf, Lila; Mapelli-Brahm, Paula; Khaled Khodja, Nabyla; Remini, Hocine; Madani, Khodir; Meléndez-Martínez, Antonio Jesús
Abstract: The carotenoid and mineral levels as well as the in vitro antioxidant capacity, using the 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay, of waste from cantaloupe was assessed. Then the matrix was subjected to ultrasound-assisted extraction (UAE) and response surface methodology (RSM) was used for the optimization of the extraction of carotenoids. The effect of the extraction procedure on the microstructure of the powder was assessed by scanning electron microscopy (SEM) analysis. The major carotenoids identified were lutein (63.24 ± 0.73 μg βCE/g dw) and β-carotene (56.43 ± 0.11 μg βCE/g dw). Several mineral elements (K, Na, P, Mg, Ca, Fe, Cu, Mn and Zn) were identified, potassium being the major one.The extract exhibited in vitro antioxidant activity (IC50  = 7.33 ± 0.22 μg/mL). The RSM results showed that an amplitude of 100%, extraction time of 10 min, hexane percentage of 80% in hexane/acetone solvent, and solvent-to-solid ratio of 55 mL/g were the optimal conditions for the extraction of carotenoids. Under these conditions, the carotenoid content of the extract was 124.61 ± 3.82 μg/g.The microscopic analysis revealed the effectiveness of the ultrasound treatment that results in noticeable physical changes, like microscopic perforations and breakages. Graphical abstract: Unlabelled Image Highlights: Optimization of carotenoid extraction from cantaloupe waste using RSM The cantaloupe waste samples contained lutein and β-carotene as major carotenoids. SEM revealed noticeable microstructural changes after ultrasound extraction. K, Na, P, Mg, Ca, Fe, Cu, Mn and Zn were identified, K being the major one. The extract exhibited an antioxidant activity (IC50 = 7.33 μg/mL) by the DPPH assay.